Chemical Expansion of Yttrium‐Doped Barium Zirconate and Correlation with Proton Concentration and Conductivity. Issue 11 (30th June 2016) - Han, Donglin; Hatada, Naoyuki; Uda, Tetsuya
Abstract : Y‐doped BaZrO3 (BZY) is a promising candidate as an electrolyte in fuel cells, and attracts increasing attention. In this work, a systematic investigation was performed on microstructure, proton concentration, proton conductivity, and hydration induced chemical expansion in Y‐doped BaZrO3 . The results revealed that the bimodal microstructure in BaZr0.85 Y0.15 O3−δ was composed of large grains with composition close to the nominal value, and fine grains with large compositional discrepancy. This property is considered to be one of the evidences of phase separation at lower temperature than sintering temperature (1600°C), which hinders the grain growth. Thermal expansion coefficient of BZY was measured for various dopant level, and was determined to be around 10 −5 K −1 in wet and dry argon atmosphere. In addition, chemical expansion effect due to hydration was confirmed by HT‐XRD in dry and wet Ar atmospheres, and suggests an interesting relationship between the lattice change ratio and proton concentration, in the BZY system with different Y content. The change ratio of lattice constant due to hydration increased obviously with the proton concentration for the sample containing the Y content of 0.02 and 0.05, but only changed slightly when the Y content was increased to 0.1 and 0.15. However, when the Y content was further increased over 0.2, the change ratio of lattice constant due to hydration starts to increase obviously again. Such results indicate a high possibility that the stable sites of protons in BZY changed with the variation in Y content.